Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - Chapters 1-2 Cumulative Review Problem Set - Page 91: 35



Work Step by Step

We first group like terms to ease simplification. We will then combine like terms to simplify the expression: $3.2a-1.4b-6.2a+3.3b$ =$3.2a-6.2a-1.4b+3.3b$ =$(3.2a-6.2a)+(-1.4b+3.3b)$ =$(-3.0a)+(-1.4b+3.3b)$ =$(-3.0a)+(1.9b)$ =$-3a+1.9b$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.